Relapsing polychondritis with large airway involvement. Issue 1 (12th November 2019) - Yu, Christiaan; Joosten, Simon A.
Abstract : Relapsing polychondritis is a rare autoimmune condition characterized by episodic and progressive cartilaginous inflammation. Its clinical presentation is vastly divergent and can affect various organs. We report the uncommon case of large airway involvement in a patient presenting with shortness of breath on the background of diagnosed relapsing polychondritis. Computed tomography (CT) chest demonstrated thickening of the cartilaginous portions of the trachea and bronchi with sparing of the posterior membranes, consistent with tracheobronchomalacia and repeated cartilaginous destruction. High doses of systemic glucocorticoids, accompanied by continuous positive airway pressure, were required for treatment. We highlight the importance of identifying the extent of airways affected and definitive positive airway pressure support for relapsing polychondritis affecting major airways in addition to conventional therapy of immunosuppression. Abstract : Relapsing polychondritis is a rare, life‐threatening, autoimmune condition. We present a previously undescribed occurrence of relapsing polychondritis with acute large airway involvement requiring short‐term positive airway pressure therapy in the context of a respiratory viral infection.